Education, disability and social policy - Haines, Steve; Ruebain, David (Policy Press, 2011)
Disability is an increasingly vital contemporary issue in British social policy & particularly so in the area of education. This volume brings together for the first time unique perspectives from leading thinkers including senior academics opinion formers, policy makers & school leaders to explore these issues.